Chemosensitizing properties of β-caryophyllene and β-caryophyllene oxide in combination with doxorubicin in human cancer cells - Di Giacomo, Silvia; Wink, Michael (Anticancer research, 2017)
BACKGROUND/AIM: The natural sesquiterpenes β-caryophyllene (CRY) and β-caryophyllene oxide (CRYO) were evaluated for their potential chemosensitizing properties. MATERIALS AND METHODS: CRY and CRYO cytotoxicity was tested against the Caco-2, CCRF/CEM and CEM/ADR5000 human cancer cell lines. Furthermore, combination experiments were carried out in order to study the ability of the sesquiterpenes to increase doxorubicin cytotoxicity. The possible interference of CRY and CRYO with functionality of ATP-binding cassette (ABC)-transporters was also investigated by Rhodamine123 efflux assay. RESULTS: Despite a low cytotoxicity, both substances were able to enhance the cytotoxicity of doxorubicin in all cell lines, with CRYO being the most effective reversal agent. Both sesquiterpenes were also able to increase the Rho123 content into cells, likely due to inhibition of the efflux pumps. CONCLUSION: Our results highlight a potential role of CRY and CRYO as new chemosensitizing agents for doxorubicin chemotherapy and to re-sensitize cancer-resistant cells.
Gesehen am 03.08.2017